The Role of Augmented Reality in Transforming Education to Support Sustainable Development Goals: A Literature Review - Sri Adelila Sari; Hanisah Hasibuan; Marudut Sinaga; Corrienna Abdul Talib (Jurnal Pendidikan Sains Indonesia, 2025)
Access to quality education remains a challenge in developing nations, including Indonesia. Augmented reality (AR) has emerged as a promising tool to address this gap. This review aimed to examine AR applications in education from 2001 to 2024, focusing on their impact on learning outcomes and accessibility. The study analyzed 171 articles selected through a systematic search in databases like scopus and IEEE explore. Key aspects reviewed include AR tools, applications, evaluation methods, and target demographics. Findings highlight ARs effectiveness in STEM education, vocational training, and cultural learning through features like 3D visualizations, interactive simulations, and animations, enhancing engagement and skill acquisition. AR aligns with sustainable development goals 4 (quality education), 9 (industry, innovation, and infrastructure), and 10 (reduced inequality) by improving access to education and reducing inequalities. However, challenges such as inadequate teacher training, limited infrastructure, and the need for localized content hinder broader implementation. The review concludes that AR tools should address pedagogical and contextual needs for optimal impact. Recommendations include expanding teacher training, improving access to technology, and developing culturally relevant content. Future research should explore scalable, long-term AR solutions to enhance global education